Is the Direct Method still Effective in Teaching English Speaking Skills in Indonesia? - Nurul Fitriyanti Thalib Abas; Z Zainurrahman (Jurnal Langua, 2022)
This study aimed to find out whether the direct method is still effective in teaching English speaking skills especially in Indonesia context. By employing a classroom action research and library research, it was found that the direct method has been underlooked by teachers and researchers in recent years. It could be seen from the decrease of publication under this theme at least the ones indexed by Google Scholar. Both the classroom action research and library research conducted suggested that the direct method is still effective in teaching English speaking skills in Indonesia. However, some suggestions were also made for the implementation of the direct method to be effective in the classrooms including the classroom activities, visual aids, and teacher’s foreign language proficiency.